IMPROVING OF STUDENTS’ SPEAKING ACHIEVEMENT THROUGH MONOPOLY GAME IN NEW NORMAL ERA (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2023)
This research aimed to prove improvement towards students’ speaking achievement through the Monopoly Game of the class X-5 students of ITP Surabaya in the year of study 2022/2023. Their poor speaking skills were the issue. Therefore, the researcher conducted a fun treatment during classroom activities in teaching speaking through Monopoly Game. The method of this study was Classroom Action Research.. The actions was done in two cycles. The data in this study was analyzed qualitatively and quantitatively. The results showed that Monopoly Game improved students' speaking skills and the improvement was shown in the test result. The percentage of students who passed the test on cycle 1 was 36% and the number of students who passed on cycle 2 rose to 84%. Observation finding showed that the students became more engaged and their activities dominate throughout the learning process. Also, the questionnaire showed students gave positive opinion that said Monopoly Game was made stuudents enjoy during classroom activities. It indicated that through Monopoly Game, the students speaking achievement was improved
Keywords: Monopoly Game; Speaking Ability; Speaking Achievement; teaching Speaking